Impact of Educational’ Interventions that Lead to the Compliance with Hand Hygiene Guidelines for Healthcare Professionals within a Hospital Care Setting in Abu Dhabi. thus, Reducing the Nosocomial’ Infections - BARRE, NURA ISMAIL (2018)
Healthcare-associated infections (HCAI) can be prevented by applying better policies, and interventions. Complete adherence to these infection control procedures is essential for the successful implementation of educational interventions (McCay, 2015). The purpose of the current study was to determine the features of structured educational interventions that impact the compliance of hand hygiene by healthcare professionals within a hospital setting. Current research work also focused hand washing practice to make it a regular practice for the healthcare. The current study has been designed in the context of HCAIs practices at the global level and HCAIs compliance levels have been reviewed. An electronic search of 16 relevant health and educational databases was performed and then augmentation of this search was done. The search gave multiple strategies and ideas (McGoldrick, 2017). Authors have applied multi-featured interventions in different studies and multiple component interventions have been found better as compared to single component interventions for better HH compliance (Saint et al., 2009). Quasi-experimental design approach has been used for the current work. This involves pre and post-intervention analyses. Current research work has been organized to develop the structured educational intervention to modify medical staff attitude towards better compliance of hand sanitation rules (Russo, 2009). The study gave interventional approach for HH compliance measurement in the hospital. The current work has devised the ways to make hand washing practices a peculiar part of medical personnel health care activities. Intervention programs, training, education, giving HH facilities, and HH reminders improved HH practices. Currently, these interventions designed according to WHO rules have brought awareness regarding the HH compliance in developing and developed regions. Hand hygiene habits must be an intrinsic part of clinical and treatment practices (Benton, 2007).